Hydrodynamic Casson hybrid nanofluid flow across a stretching sheet in the regime of velocity slip and temperature jump,including viscous dissipation, melting, Soret and Dufour effects - B. Laxmia; Dr. Khem Chand; Dr Pankaj Thakur (Journal of Nigerian Society of Physical Sciences)
This work explores the magnetohydrodynamics (MHD) viscous, incompressible, Casson hybrid nanofluid over a stretched sheet which is a well-known non-Newtonian fluid. The analysis incorporates the effects of viscous dissipation, melting, Soret and Dufour effects, within the frameworks of velocity slip and temperature jump boundary conditions. Copper (Cu) and alumina oxide (Al2 O3 ) have been employed as nanoparticles, while water (H2 O) has been considered as the base fluid. This mixture is used to increase the fluid’s thermal characteristics for better heat transfer efficiency. To simplify the complex governing partial differential equations describing the flow and heat transfer characteristics, similarity transformations were employed, which reduced the system to a set of coupled, ordinary differential equations that are nonlinear. The bvp4c function in MATLAB was used to solve these modified equations numerically. The study looks into the effects of various parameters on flow and heat transfer characteristics, such as the volume fractions of alumina and copper, the Prandtl Number, the Radiation parameter, the Darcy permeability, the Magnetic field parameter, the heat source/sink parameter, melting parameter, the Eckert Number, the Soret number, and the Dufour number. Results indicate that the alumina volume fraction influences the velocity, temperature and concentration profiles. Specifically, the aluminium oxide volume fraction parameter causes increases in profiles of temperature, velocity and concentration. With suction and the Casson parameter, the mass transfer rate increases while the heat transfer rate decreases.